Dipole-Fed Rectangular Dielectric Resonator Antennas for Magnetic Resonance Imaging at 7 T: The Impact of Quasi-Transverse Electric Modes on Transmit Field Distribution - Wenz, Daniel; Gruetter, Rolf (Frontiers in Physics, 2021)
Shortened dipole antennas based on rectangular dielectric blocks play important role in ultrahigh field magnetic resonance imaging (UHF-MRI) radio frequency (RF) coil design. However, the generally assumed direct contact with the subject is difficult to maintain in typical in vivo settings. We have previously observed that particular dielectrically-shortened dipole antennas can produce a substantially altered transmit field distribution with a very low transmit efficiency when the block and the sample were physically separated. Therefore, the aim of this study was to determine (a) why different designs of dielectrically-shortened dipole antennas can produce inefficient transmit field when the block and the sample are physically separated, and (b) how this depends on key parameters such as rectangular block geometry, dielectric constant, loading geometry and RF feeding. In this work, two main types of quasi-transverse dielectric modes were found in different rectangular block geometries and interpreted as TE11δz (MR-efficient) and TE1δδy (MR-inefficient) and their impact on in vivo MRI experiments involving human head, calf and wrist was explored. This study shows for the first time why certain antennas preserve their transmit field efficiency despite physical separation from the sample. We conclude that the proposed approach has potential to provide new insights into dipole antenna design for UHF-MRI.